182k views
4 votes
1.) The length of the missing side is?

2.) What is the length of the missing side?

1.) The length of the missing side is? 2.) What is the length of the missing side-example-1
1.) The length of the missing side is? 2.) What is the length of the missing side-example-1
1.) The length of the missing side is? 2.) What is the length of the missing side-example-2
User Andsens
by
6.3k points

2 Answers

5 votes
To find the hypotenuse the formula would be:

c^2 = a^2 + b^2

BUT! These two questions ask for the length of the smaller sides, so we need to rearrange the formula to:

a^2 = c^2 - b^2

Where c is the hypotenuse, and b is the other known length. Use this formula to solve the length of the unknown side.

Let's call the unknown side x,

1) a^2 = c^2 - b^2
x^2 = 17^2 - 15^2
x^2 = 64
Square root both sides to get x
x = 8

2) a^2 = c^2 - b^2
x^2 = 26^2 - 24^2
x^2 = 100
Square root both sides to get x
x = 10

Hope this helped! Ask me if there's any part of the working you don't understand :)
User Fred
by
6.9k points
4 votes
a^2 + b^2 = c^2
a^2 + 15^2 = 17^2
a^2 + 225 = 289
a^2 = 289 - 225
a^2 = 64
sqrt of 64 = 8
a = 8
x = 8
User Tjallo
by
6.3k points